Larus canus - Valverde G?mez, Jos? Antonio, 1926-2003
Cuatro observaciones de la Gaviota cana (Larus canus) realizadas durante sendas salidas de campo a diferentes enclaves de la provincia de Valladolid entre el 29 de enero de 1947 y el 15 de febrero de 1956. Four observations of the Mew Gull (Larus canus) carried out through field trips to different habitats of the province of Valladolid between the 29th of January of 1947 and the 15th of February of 1956.